Novel gas sensor with dual response under CO(g) exposure: Optical and electrical stimuli - Rocha, L. S. R. (2018)
In this work, a lanthanum (La) doped ceria (CeO2) film, which depicted a dual gas sensing response (electric and optical) for CO(g) detection, was obtained by the microwave-assisted hydrothermal (HAM) synthesis and deposited by the screen-printing technique, in order to prevent deaths by intoxication with this life-threatening gas. An electric response under CO(g) exposure was obtained, along with an extremely fast optical response for a temperature of 380 °C, associated with Ce+4 reduction and vacancy generation. A direct optical gap was found to be around 2.31 eV from UV–Vis results, which corresponds to a transition from valence band to 4f states. Due to the anomalous electron configuration of cerium atoms with 4f electrons in its reduced state, they are likely to present an electric conduction based on the small polaron theory with a hopping mechanism responsible for its dual sensing response with a complete reversible behaviour.